E-160 Detailed evaluation of brain cone-beam CT imaging artifacts: a prospective stroke series. (23rd July 2022) - Cancelliere, N; Hummel, E; van Nijnatten, F; Nicholson, P; van Vlimmeren, M; Hallacoglu, B; Mendes Pereira, V
Abstract : Background: Cone-beam computed tomography (CB-CT) imaging of the head can be acquired in the angiography suite to support various neurovascular procedures. Sole reliance on this imaging, however, still lacks full diagnostic confidence for stroke assessment due to various imaging artifacts that persist, even with the latest CB-CT technology. Purpose: The purpose of this study was to perform a detailed evaluation of image artifacts present on our series of advanced head CB-CT scans and evaluate improvements using a new CB-CT protocol which implements a novel dual-axis 'butterfly' trajectory. Methods: We included 94 scans from 47 patients who received CB-CT imaging for ischemic or hemorrhagic assessment during a neurovascular procedure. Both a single-axis 'circular' and novel dual-axis 'butterfly' protocol were performed on each patient as an intra-patient control. Each brain scan was divided into six regions and scored out of 3 based on six imaging artifacts originating from various physics- and patient-based sources ( Figure 1 ). Results: Overall, the dual-axis trajectory produces CB-CT images with significantly less image artifacts than the advanced circular scan (whole brain average artifact score, AS: 0.20 vs. 0.33). Greatest improvements were seen for bone beam hardening (AS: 0.13 vs. 0.78) and cone-beam artifacts (AS: 0.04 vs. 0.55). Conclusions: Recent developments in CB-CT imaging protocols have significantly improved image artifacts, which has improved diagnostic confidence for stroke and support a direct-to-angiosuite transfer approach for acute ischemic stroke patients. Disclosures: N. Cancelliere: None. E. Hummel: 5; C; Philips. F. van Nijnatten: 5; C; Philips. P. Nicholson: None. M. van Vlimmeren: 5; C; Philips. B. Hallacoglu: 5; C; Philips. V. Mendes Pereira: 1; C; Philips.